A first-principles study on the B5O5+/0 and B5O5− clusters: The boron oxide analogs of C6H5+/0 and CH3Cl - Tian, Wen-Juan; You, Xue-Rui; Li, Da-Zhi; Ou, Ting; Chen, Qiang; Zhai, Hua-Jin; Li, Si-Dian (The Journal of chemical physics, 2015)
The concept of boronyl (BO) and the BO/H isolobal analogy build an interesting structural link between boron oxide clusters and hydrocarbons. Based upon global-minimum searches and first-principles electronic structural calculations, we present here the perfectly planar C2v B5O5+ (1, 1A1), C2v B5O5 (2, 2A1), and tetrahedral Cs B5O5− (3, 1A′) clusters, which are the global minima of the systems. Structural and molecular orbital analyses indicate that C2v B5O5+ (1) [B3O3(BO)2+] and C2v B5O5 (2) [B3O3(BO)2] feature an aromatic six-membered boroxol (B3O3) ring as the core with two equivalent boronyl terminals, similar to the recently reported boronyl boroxine D3h B6O6 [B3O3(BO)3]; whereas Cs B5O5− (3) [B(BO)3(OBO)−] is characterized with a tetrahedral B− center, terminated with three BO groups and one OBO unit, similar to the previously predicted boronyl methane Td B5O4− [B(BO)4−]. Alternatively, the 1–3 clusters can be viewed as the boron oxide analogs of phenyl cation C6H5+, phenyl radical C6H5, and chloromethane CH3Cl, respectively. Chemical bonding analyses also reveal a dual three-center four-electron (3c-4e) π hyperbond in Cs B5O5− (3). The infrared absorption spectra of B5O5+ (1), B5O5 (2), and B5O5− (3) and anion photoelectron spectrum of B5O5− (3) are predicted to facilitate their forthcoming experimental characterizations. The present work completes the BnOn+/0/− series for n = 1–6 and enriches the analogous relationship between boron oxides and hydrocarbons.